Triggering acute pancreatitis complicated with acute myocardial infarction by marijuana: a rare case report - Hajimoradi, Behzad; Safi, Morteza; Pishgahi, Mehdi; Alirezaei, Toktam; Jebreil Mosavi, Mirjafar (Acta Biomedica Atenei Parmensis, 2021)
ABSTRACTMarijuana is a widely used illicit substance among young adults and its abuse has been reported worldwide. Marijuana is a rare trigger of acute myocardial infarction and acute pancreatitis.We present a 25-year-old man with acute pancreatitis subsequently complicated by acute ST-elevation myocardial infarction (STEMI), which was associated with marijuana abuse. This case highlights the need and importance of awareness among public about this rare but potentially lethal adverse effect. Also, it draws attention when clinicians confront patients with history of substance abuse, they should be alert to the possibility of concurrent occurrence of serious medical conditions that may be adverse effects of substance use.Acute pancreatitis with concurrent acute STEMI is a rare situation but is a challenge for many emergency physicians, and it can lead to trouble outcomes if it not be quickly diagnosed and properly managed. We demonstrate successful management in this complicated patient with primary angioplasty.